2019
DOI: 10.21608/edj.2019.72868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticles Modified Glass Ionomer Cement on the Colour and Shear Bond Strength of Lithium Disilicate Ceramic

Abstract: The effect of glass ionomer cement modified by nanoparticles on the bond strength and colour of lithium disilicate ceramic was studied. Glass ionomer cement modified by nanosilver or nanogold, glass ionomer cement and IPS e.max CAD A2 were used. Thirty e.max CAD discs were constructed. The samples were divided into 3 groups, the first group, 10 samples (control group) used non modified glass ionomer cement (GIC), the second and third groups, 10 samples each used modified glass ionomer cement : nano silver (NSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Nevertheless, we used 10% polyacrylic acid to condition the dentin, which causes the partial removal of the smear layer and the demineralization of the upper surface dentin, thereby enabling the establishment of micromechanical adhesion and the formation of a shallow hybrid layer, which leads to the improvement of the bond strength (Nicholson, 2016 ). It is also worth noting that we used the SBS test because chewing forces around the mouth are a combination of compressive, tensile, and shear that are applied to the restorative material and tooth tissue, but most of them include shear forces (Salem & Asaad, 2019 ). It can be predicted that if micro‐tests are used instead of macro, much higher bond strength values are obtained (Ismail et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we used 10% polyacrylic acid to condition the dentin, which causes the partial removal of the smear layer and the demineralization of the upper surface dentin, thereby enabling the establishment of micromechanical adhesion and the formation of a shallow hybrid layer, which leads to the improvement of the bond strength (Nicholson, 2016 ). It is also worth noting that we used the SBS test because chewing forces around the mouth are a combination of compressive, tensile, and shear that are applied to the restorative material and tooth tissue, but most of them include shear forces (Salem & Asaad, 2019 ). It can be predicted that if micro‐tests are used instead of macro, much higher bond strength values are obtained (Ismail et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the shear bond strength is significant specially when dealing with considerably brittle materials like GICs (33) .In the present study, the obtained results showed a slight but statistically insignificant increase in the value of shear bond strength with increasing concentration of ZrO 2 NPs and this agree with previous study done by Rezvani (33) and Garcia -contreras et al (34) , who explained that addition of nanoparticles to GIC cement basic powder, does not influence the shear bond strength, this could be explained by the presence of low attraction ionic force between additive particles and luting cement base powder, And this could be due to the fact that the nanoparticles may act as an inert particle forming obstacles that enhance crack formation, Nanosized particles can occupy and fill the empty gaps and spaces between the larger sized glassionomer powder particles (35) and provide extra site for bonding with the polymer matrix (36) or the added nano-size particle allows their dispersion without any significant geometric matrix change between and around polymer chains of the cement.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of factors affect the durability of the restoration as; structure of tooth surface, preparation and design, the used ceramic type, the type of cement used, tooth morphology and functional and parafunctional activities of the patient (5) .…”
Section: Introductionmentioning
confidence: 99%